The organization of an educational program for specialists in Clinical Chemistry by the Greek Society of Clinical Chemistry-Clinical Biochemistry - Rizos, D.; Karababa, P.; Sarandakou, A.; Panagiotakis, O.; Haliassos, A.; Makris, K.; Psarra, K.; Bairaktari, E.; Spyropoulou, P.; Nikolou, C.; Galiatsatos, N.; Trakas, N.; et al. (Biochemia Medica, 2011)
In Greece, there is no officially organized training in clinical chemistry for scientists. The Greek Society of Clinical Chemistry-Clinical Biochemistry decided to organize an intensive educational program of 18 seminars on clinical chemistry content as it is described in the EC4 Syllabus. The duration of each seminar was about 6 hours and consisted of 6 to 9 lectures. At the end of each seminar there was a voluntary written examination, comprised of 24 multiple choice questions. Successful completion of the Educational program was leading to a Certificate of Competence. Two cycles of the 18 seminars were performed: 1st cycle from October 2003 to December 2005 and 2nd cycle from March 2005 to October 2007. One hundred eighty nine colleagues was the mean attendance per seminar for the seminars of the 1st cycle and 38 colleagues for the seminars of the 2nd cycle. The mean participation to the examination for each seminar was almost 80% for the 1st cycle and 68% for the 2nd cycle. More than 80% of the participants performed Good or Very good in the examination in both cycles. It is estimated that more than 40% of the scientists who practice Clinical Chemistry in Greece, participated to this educational activity. This program is now provided as an e-learning application, and it is open for all scientists who want to follow the discipline of clinical chemistry.
Keywords: Clinical chemistry; EC4; Education; register